Вы находитесь на странице: 1из 33

.

26 2013

f (x) ,
(a, b). F (x), F 0 (x) = f (x)
x 2 (a, b),
f (x).
,
f (x) = x 2 , F (x) = x 3 /3,
f (x) = sin x, F (x) =

cos x.

:

,

.
.


( )
(a, b)
.
( )
F (x) f (x),
F (x) + C, C , .
.
Example
arctg x arctg(1/x)
1/(1 + x 2 ). ? ?


Z
f (x) dx = F (x) + C,

x 2 (a, b)

f (x).
Z
x3
Example:
x 2 dx =
+ C.
3

.
, .

x +1
x dx =
+ C, 6= 1.
+1
Z
R
Rp
dx R p
x 2 dx,
x dx,
, x 3 x dx.
x2
Z
p
x dx
p
,
= 1 + x2 + C
1 + x2
Z
sin4 x
,
sin3 x cos x dx =
+ C.
4
,


Z
1
d f (x) dx = f (x) dx
Z
2
dF (x) = F (x) + C

Z
Z
1
Af (x) dx = A f (x) dx
Z
Z
Z
2
(f (x) + g(x)) dx = f (x) dx + g(x) dx

Z
Z
Z
Z
Z
Z
Z

x n dx =

x n+1
+C
n+1

(n 6=

1)

dx
= ln |x| + C, ( 1, 0) (0, 1)
x
dx
= arctg x + C
1 + x2
dx
1
x
= arctg + C
a2 + x 2
a
a
dx
1
a+x
=
ln
+ C ( )
a2 x 2
2a
a x
dx
x
p
= arcsin + C
2
2
a
a
x
p
dx
p
= ln x + x 2 a2 + C
x 2 a2
.

ex dx = ex + C

sin x dx =

Z
Z

ax dx =

ax
+ C, (a > 0, a 6= 1)
ln a
cos x + C

cos x dx = sin x + C

dx
= tg x + C
cos2 x
Z
dx
= ctg x + C
sin2 x

.
!
.

,
.

.


,
. :
Z

x 2 dx
=
1 + x2

Z
x2 + 1 1
dx
=
1
1 + x2
Z
Z
= dx

1
dx
1 + x2
dx
= x arctg x + C.
1 + x2

Z
Z

(x 2

1)3 dx =

(x 2

1)3
x2

x2

dx =

x6

3x 4 + 3x 2

3x 2 + 3

x4

1 dx =

1
x2

x7
7

dx =

x5
5

3x 5
+ x3
5

x 3 +3x +

x + C.

1
+C.
x

p
3x
2 p
dx =
x 3/2 3x 1/2 dx = x 2 x 2x x + C.
5
x

Z
Z
1
tg2 x dx =
1 dx = tg x x + C.
cos2 x


Example

a = 4 (/c). x = x(t),
t = 0 .
1

v 0 (t) = a,
v (t) =

a(t) dt = at + C.

v = 0 t = 0, C = 0. v (t) = at = 4t.
2

x 0 (t) = v (t) = 4t,


Z
Z
x(t) = v (t) dt = 4t dt = 2t 2 + C1 .
, x(0) = 0, C1 = 0, x(t) = 2t 2 .
.

()

f (x) dx = F (x) + C.

u = u(x)
Z
f (u) du = F (u) + C.
.
:
Z
f (u)u 0 dx = F (u(x)) + C.

F (u) = u 2
Z

sin2 x cos x dx =

0
u2 u
dx} =
| {z
du

u 2 du =

u3
sin3 x
+C =
+ C.
3
3

sin2 x dx )

II
p
F (u) = 1/ 1

u2
du

x dx
1

x4

z }| {
u 0 dx
p
1 u2

1
2x dx
1
p
=
4
2
2
1 x
Z
1
du
1
1
p
=
= arcsin u + C = arcsin(x 2 ) + C
2
2
2
1 u2
=

Z
x dx
1
du
2
=
x
=
u
=
.
2
4
1+x +x
2
1 + u + u2

. I

x = '(t)
f (x) , x = '(t)
.
Z
Z
f (x) dx = f ('(t))'0 (t) dt.

x, ,
'(t) .

. II

Example
Z

Z
Z
dx
2t dt
(t + 1 1) dt
p = x = t2 =
=2
1+t
1+t
1+ x

Z
1
=2
1
dt = 2(t ln |1 + t|) + C
1+t
p
p
= 2( x ln 1 + x ) + C.

I

u v ,
Z
Z
u dv = uv
v du.
:
Z

u = x,
sin x dx = dv
v = cos x,
du = dx
Z
= x( cos x)
( cos x)dx = x cos x + sin x + C.

x sin x dx =

II



P(x)ekx , P(x) cos kx, P(x) sin kx,
P(x) , P(x) = a0 x n + a1 x n

P(x) ln kx, P(x) arctg kx, P(x) arcsin kx.

+ ,

,
.

.
.


,
, ,
.
x.

P(x)
f (x) = R(x) =
,
Q(x)
P(x) Q(x) , ..
P(x) = a0 x m + a1 x m

+ + am ,

Q(x) = b0 xn + b1 x n

+ + bn .

,
, ,
m < n, .




( ).
,

A
1
,
x a
A
2
,
(x a)k
Ax + B
3
,
2
x + px + q
Ax + B
4
.
(x 2 + px + q)k
.

I

, ..

x a x 2 + px + q.
x 2 + px + q
, p2 4q < 0.
Example
x 4 + 4 = x 4 + 4x 2 + 4

4x 2 = (x 2 + 2)2

4x 2

= (x 2 + 2x + 2)(x 2

2x + 2).


,
.
.

II

(m < n)
. :

(x

P(x)
A1
Ak
=
+ +
+
l
+ px + q)
x a
(x a)k
M 1 x + N1
M l x + Nl
+ 2
+ + 2
+
x + px + q
(x + px + q)l

a)k (x 2

,
.

Example
x3

x
x
=
+1
(x + 1)(x 2

x + 1)

A
Bx + C
+ 2
.
x +1 x
x +1

,
x = A(x 2 x +1)+(Bx +C)(x +1) = (A+B)x 2 +( A+B +C)x +A+C.
x,

8
>
< 0 = A + B,
1 = A + B + C,
>
:
0 = A + C.

, A = 1/3, B = C = 1/3. ,

x
1
1
x +1
=
+
.
x3 + 1
3
x + 1 x2 x + 1



A1
Ak
,
x a
(x a)k
, ,
Z
A1
dx = A ln |x a| + C.
x a
.

Z
x dx
I=
.
x 2 + 4x + 5

Z
Z
x dx
t 2
I=
=
x
+
2
=
t
=
dt
2
(x + 2) + 1
t2 + 1
1
1
= ln(t 2 +1) 2 arctg t +C = ln((x +2)2 +1) 2 arctg(x +2)+C.
2
2
.